Light microscopy and computer three-dimensional reconstruction of the blood capillaries of the enamel organ of rat molar tooth germs - Cerri, Paulo Sérgio [UNESP]; de Faria, F. P.; Villa, R. G.; Katchburian, E. (Blackwell Publishing, 2004)
We performed a light microscope and a computer three-dimensional reconstruction study of serial sections of the molar enamel organ of 3- and 5-day-old rats perfused with Indian ink through the arterial system. The tooth germs were fixed in Bouin's solution, embedded in paraffin, sectioned and stained with haematoxylin and eosin. For the three-dimensional reconstruction, light micrographs of the serial sections were digitized, and aligned using the serial EM Align software downloaded from http://synapses.bu.edu/tools/. After alignment, the boundaries of the India-ink-filled blood vessels were manually traced with a mouse using the software IGL trace (version 1.26b), also downloaded from the above website. After tracing, a three-dimensional representation of the blood vessel contours was generated in a VRML format and visualized with the help of the software Cortona Web3D viewer (version 4.0) downloaded from http://www.parallelgraphics.com/products/cortona. Our results showed that in regions where ameloblasts are polarized the capillaries are arranged in three distinct levels: (1) penetrating and leaving capillaries in relation to the outer enamel epithelium; (2) capillaries crossing and branching inside the stellate reticulum; and (3) capillaries branching and anastomosing profusely within the stratum intermedium, thereby forming an extensive capillary plexus intimately associated with the cells of the stratum intermedium. The existence of a conspicuous capillary plexus intermingled with cells of the stratum intermedium, as shown in our results, suggests that some molecules produced by cells of the stratum intermedium could be released into the capillary plexus and thereafter carried to the dental follicle.
Keywords: capillaries; computer reconstruction; enamel organ; stellate reticulum; tooth germ